Using a real-life case scenario to integrate additional health professions students into an existing interprofessional team seminar. Issue 2 (3rd March 2016) - Pole, David; Breitbach, Anthony P.; Howell, Timothy G.
ABSTRACT: The World Health Organization stated that the goal of interprofessional education (IPE) is to prepare students as collaboration-ready members of interprofessional care teams. Educators try to create meaningful and relevant learning experiences for multiple health professions students. A longitudinal Interprofessional Team Seminar (IPTS) course includes over 650 students from seven health professions at the professional training level. Recommendations from the National Athletic Trainers' Association (NATA) promote the inclusion of athletic training (AT) students in IPE initiatives. A new IPTS module included AT students focusing on the attributes of rapidly forming and different care teams as the patient transitions from an on-field injury, to acute care, inpatient care, and rehabilitative care, and back to activities of daily living. Qualitative review of reflections from the students assessed the impact of these IPTS modules. The intentional design of this course, focusing on behaviours of collaborative practice and supporting students to be collaboration ready, effectively introduced and highlighted profession-specific strengths and unique contributions to team-based care.